2021
DOI: 10.3390/ijms22126506
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of the Role of Long Non-Coding RNAs in Human Choriocarcinoma

Abstract: Choriocarcinoma (CC), a subtype of trophoblastic disease, is a rare and highly aggressive neoplasm. There are two main CC subtypes: gestational and non-gestational, (so called when it develops as a component of a germ cell tumor or is related to a somatic mutation of a poorly differentiated carcinoma), each with very diverse biological activity. A therapeutic approach is highly effective in patients with early-stage CC. The advanced stage of the disease also has a good prognosis with around 95% of patients cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 123 publications
(134 reference statements)
0
8
0
Order By: Relevance
“…Similar to messenger RNAs, they are involved in the pathogenesis of cancer [ 11 , 13 , 14 , 15 , 16 , 17 , 18 ]. Different classes of lncRNAs are generated from introns, exons, intergenic regions, telomerases, enhancers, or promoters [ 19 ]. Of the approximately 60,000 lncRNAs identified in human tumor tissues and cancer cell lines, the role and regulatory mechanisms of the majority of lncRNAs are still largely unknown.…”
Section: Long Non-coding Rnas and Potential Therapeutic Targeting In ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to messenger RNAs, they are involved in the pathogenesis of cancer [ 11 , 13 , 14 , 15 , 16 , 17 , 18 ]. Different classes of lncRNAs are generated from introns, exons, intergenic regions, telomerases, enhancers, or promoters [ 19 ]. Of the approximately 60,000 lncRNAs identified in human tumor tissues and cancer cell lines, the role and regulatory mechanisms of the majority of lncRNAs are still largely unknown.…”
Section: Long Non-coding Rnas and Potential Therapeutic Targeting In ...mentioning
confidence: 99%
“…For example, HOX antisense intergenic RNA (HOTAIR) is one of the most well-studied oncogenic lncRNAs involved in the carcinogenesis of several types of cancer. An elevated HOTAIR expression is associated with resistance to chemotherapeutics, suggesting that inhibitors of HOTAIR could potentially resensitize a patient’s tumor to a specific chemotherapy [ 19 , 22 , 23 , 24 ]. One of the first-identified lncRNAs, H19, acts as a decoy for several tumor-suppressor miRNAs [ 25 ].…”
Section: Long Non-coding Rnas and Potential Therapeutic Targeting In ...mentioning
confidence: 99%
“…The most comprehensive study, to date, analyzed >7,000 RNA-seq libraries and identified >7,000 cancer-associated lncRNAs (Sun, 2015). (Di Fiore et al, 2021;Ebrahimi et al, 2021;Huang & Tang, 2021;Lanzafame et al, 2018;Sun, 2015;Xi et al, 2017).…”
Section: Fragmentation Of Rna-seq Databases and Standardsmentioning
confidence: 99%
“…The most comprehensive study, to date, analyzed >7,000 RNA‐seq libraries and identified >7,000 cancer‐associated lncRNAs (Sun, 2015 ). Several promising lncRNA candidates include prostate cancer‐associated 3 ( PCA3 ) and SWI/SNF complex antagonist associated with prostate cancer 1 ( SChLAP1 ) (specific markers for prostate cancer which can be identified in urine); hepatocellular carcinoma upregulated long noncoding RNA ( HULC ) in pancreatic cancer; lung cancer‐associated lncRNA 1 ( LCAL1 ) in lung carcinomas; H19 imprinted maternally expressed transcript ( H19 ), hepatocellular carcinoma upregulated EZH2‐associated long noncoding RNA ( HEIH ), HOX transcript antisense RNA ( HOTAIR ), and HOXA distal transcript antisense RNA ( HOTTIP ) in hepatocellular carcinoma; long intergenic non‐protein coding RNA 261 ( LINC00261 ) and PCA3 in choriocarcinoma; and ADAMTS9 antisense RNA 2 ( ADAMTS9‐AS2 ), HOXA11 antisense RNA ( HOXA11‐AS ), and cancer susceptibility 2 ( CASC2 ) in glioma (Di Fiore et al, 2021 ; Ebrahimi et al, 2021 ; Huang & Tang, 2021 ; Lanzafame et al, 2018 ; Sun, 2015 ; Xi et al, 2017 ). Recent research has shown that circRNAs—which (1) are dysregulated in a tumor‐specific manner, (2) display stage‐specific expression patterns, and (3) are more stable than linear RNAs due to their circular conformation—could be used as diagnostic markers for lung, liver, colorectal, gastric, and bladder cancers (Sawaki et al, 2018 ; Solé et al, 2021 ).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Choriocarcinoma is a malignant neoplasm composed of mononuclear cytotrophoblasts and multinucleated syncytiotrophoblasts, typically seen in childbearing-age women. [3][4][5][6][7][8][9][10] Our reported case is the first primary pancreatic choriocarcinoma patient who was accompanied by liver metastases. We highlight the role of 18 F-FDG PET/CT in identifying the stage of the tumor as well as liver and regional small lymph node metastases via the glucose metabolic information.…”
mentioning
confidence: 99%